Rescue of a recurrence of rectal adenoma using the endoscopic intermuscular dissection technique - Latorre, Gonzalo (2025)
Endoscopic intermuscular dissection (EID) emerges as an alternative for the treatment of patients with rectal lesions with suspected deep invasion or with extensive fibrosis which are not candidates for endoscopic submucosal dissection (ESD). In EID the dissection is performed between the inner (circular) and outer (longitudinal) layers of the muscularis propia. We present the case of a patient successfully treated with EID technique. 54-year-old female patient with a history sessile adenomatous lesion of the rectum of approximately 40 mm resected with conventional endoscopic mucosal resection technique. She presented a recurrence of the lesion on the prior resection scar. EID was performed on the scar of prior endoscopic resection, accessing and exposing the intermuscular plane. En bloc resection of the lesion was achieved with negative histological lateral and deep margins, fulfilling criteria for curative resection. Endoscopic resection techniques offer advantages over radical proctectomy, allowing preservation of anorectal function with lower morbidity and mortality. EID has shown effectiveness and safety in prospective studies and case report when ESD is not feasible due to technical limitations. However, further studies are required to evaluate the long-term efficacy and its comparison with other resection techniques.